Differences In Competency Of Islamic Religious Education Teachers Before And After Being Given Training In Creating Digital Learning Media - Setiawan, Hasrian Rudi; Limbong, Isman Efendi (Yayasan Rahmat Islamiyah, 2023)
This research generally aims to find out how big the difference is in the competence of religious teachers before and after training in creating digital learning media. This research was conducted at the Rahmat Islamiyah Foundation, Medan. The research method used in this research is a quantitative research method and the data collection techniques used in this research are observation and documentation. The sample in this research were all teachers at the Rahmat Islamiyah Medan Foundation. Meanwhile, the data analysis technique used in this research is descriptive and inferential statistical analysis. This research produced findings including: 1) Teacher competency in using learning media before training in digital media creation was an average of 56; 2) Teacher competency in using learning media after training in digital media creation averages 87. 3) Digital media creation training has a positive impact on the competency of religious teachers in using learning media.